La Transformación del Derecho Moderno y su incidencia en la concepción del Derecho Tributario - Durán Rojo, Luis Alberto (2015)
This article analyzes the process of paradigm change in Law, a non-peaceful transition from a model developed in the XX century to a new law which will sit throughout the XXI century. The changes that have occurred from this new legal paradigm are not superficial, but rather crossing the structures and foundations of modern legal ideology and technique that underlies, as the constitutionalization of national law, the internationalization of economic relations, the development of treaties or development of Community law. Furthermore, the author refers to the impact that this change took place in the theoretical construction of taxes and the delimitation of the scope of the tax phenomenon.